Vicegerency of the Perfect man in Islamic mysticism - Asadullah Shukriyan (حکمت اسرا, 2009)
The concept of vicegerency is a key concept in Islamic studies in general and in Islamic mysticism in particular. The present article deals with the concept of vicegerency in Islamic mystical sources comparing it with that in Islamic studies. In other words, the author tries to explain the position of the vicegerency of man, showing that mystical vicegerency is nothing other than the vicegerency explicitly mentioned in Islamic sources.